Implementasi Sistem Manajemen Arsip Direktorat Keuangan Berbasis Web ( Studi Kasus : Universitas Teknologi Sumbawa ) - Amri, Fahrul; Suparman, Suparman; Darmawan, Indra (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
For an Institution/Agency, archiving is not new. The entry and exit of documents and other documents in an agency / institution certainly requires filing. The storage carried out at the Directorate of Finance, Sumbawa University of Technology has not been effective enough for the current filing, because the filings carried out are still some done manually so that it is easy to lose archives before filing. The purpose of this study is to design a Web-based records management information system to help the filing process at the Directorate of Finance, Sumbawa University of Technology run more effectively and efficiently. The research method used in this study is a qualitative method with data collection methods used in the form of observation, interviews, documentation and literature studies. While the method used for software development or system design uses the waterfall method, where this waterfall method is a type of application development model and is included in the classic life cycle. (classical life cycle), in which this cycle emphasizes on sequential and systematic phases. The results of this study are based on a Web-based archive management information system, and data storage is more effective, the archive process is more efficient and makes it easier to search for the desired documents.